(1220) Foreign Trade Planning تخطيط التجارة الخارجية - Grote, Gerhard (The Institute Of National Planning., 2018)
Economic growth, equilibrium and effectivity of the economy as a whole are to a high extent influenced by the development of volume and structure of foreign trade. For this planning export and import as a part of national reproduction process is necessary and the implementation of a practicable and effective framework of foreign trade planning is an important and actual task.